Kerjasama World Wide Fund for Nature (WWF) dan Pemerintah Indonesia terhadap Perdagangan Satwa Ilegal - Ramadhan Dwi Januarfitra, Akhmad Riyadh Masyhadi, Dhimas Dwi Okta, Syeva Yasid Ramadhan (UIR Press, 2021)
Indonesia is a country that has diverse natural resources. However, this natural wealth has become the target of irresponsible individuals who hunt and sell liars. Borders also result in the extinction of wild liars and their habitats are also damaged. Various types of animals that are protected and endangered are still supported by Indonesia. The regulation on trade in protected animals in Indonesia is contained in Law No. 5 of 1990 concerning Conservation of Biological Natural Resources and their Ecosystems. The legal umbrella used as a reference is not implemented properly. Law enforcement and supervision need to be carried out by various elements of society in preserving Indonesia's nature. One of the supports in supervising the enforcement of the umbrella of wildlife protection is WWF as INGO (International Non-Government Organization) in collaboration with the Indonesian government in alleviating the problem of poaching and using its capabilities as an instrument that functions positively towards the preservation of fauna in Indonesia.